Dimethyl Sulfoxide Perturbs Cell Cycle Progression and Spindle Organization in Porcine Meiotic Oocytes. - Xuan Li; Yan-Kui Wang; Zhi-Qiang Song; Zhi-Qiang Du; Cai-Xia Yang (PLoS ONE, 2016)
Meiotic maturation of mammalian oocytes is a precisely orchestrated and complex process. Dimethyl sulfoxide (DMSO), a widely used solvent, drug, and cryoprotectant, is capable of disturbing asymmetric cytokinesis of oocyte meiosis in mice. However, in pigs, DMSO's effect on oocyte meiosis still remains unknown. We aimed to evaluate if DMSO treatment will affect porcine oocyte meiosis and the underlying molecular changes as well. Interestingly, we did not observe the formation of the large first polar body and symmetric division for porcine oocytes treated with DMSO, contrary to findings reported in mice. 3% DMSO treatment could inhibit cumulus expansion, increase nuclear abnormality, disturb spindle organization, decrease reactive oxygen species level, and elevate mitochondrial membrane potential of porcine oocytes. There was no effect on germinal vesicle breakdown rate regardless of DMSO concentration. 3% DMSO treatment did not affect expression of genes involved in spindle organization (Bub1 and Mad2) and apoptosis (NF-κB, Pten, Bcl2, Caspase3 and Caspase9), however, it significantly decreased expression levels of pluripotency genes (Oct4, Sox2 and Lin28) in mature oocytes. Therefore, we demonstrated that disturbed cumulus expansion, chromosome alignment, spindle organization and pluripotency gene expression could be responsible for DMSO-induced porcine oocyte meiotic arrest and the lower capacity of subsequent embryo development. Our results provide new insights on DMSO's effect on porcine oocyte meiosis and raise safety concerns over DMSO's usage on female reproduction in both farm animals and humans.